DEVOTEE OBSESSED BY THE IDEA OF RETURNING TO UKRAINE OF BOGDAN LEPKY - Скальська, У. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
An author tells about the life and patron and organizational activity of art of the known doctor, Ukrainian connoisseur, culturelogy and publicman of Ukrainian society in the USA of doctor Roman Smyk. The review of reserve of large devotee on the Lepciv field and patron of art of the Ukrainian culture is given.